1999
DOI: 10.1007/bf01434994
|View full text |Cite
|
Sign up to set email alerts
|

Nonverbal communication interface for collaborative virtual environments

Abstract: Abstract:Nonverbal communication is an ~mportant aspect of real-life face-to-face interaction and one of the most efficient ways to convey emotions, therefore users should be provided the means to replicate it in the virtual world. Because articulated embodiments are well suited to provide body communication in virtual environments, this paper first reviews some of the advantages and disadvantages of complex embodiments. After a brief introduction to nonverbal communication theories, we present our solution, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(52 citation statements)
references
References 13 publications
0
51
0
1
Order By: Relevance
“…Our main question is the extent to which proxemics behavior might be observed in virtual reality, giving credence to the view that people tend to respond realistically to virtual events and situations. From the existing literature it seems that this is likely to be the case -see for example, [Bailenson, Blascovich, Beall and Loomis 2003;Bailenson, Blascovich, Beall and Loomis 2001;Blascovich 2002;Blascovich et al 2002;Friedman et al 2007;Guye-Vuilleme et al 1999;Wilcox, Allison, Elfassy and Grelik 2006].…”
Section: If People Have This Illusion and Ifmentioning
confidence: 99%
“…Our main question is the extent to which proxemics behavior might be observed in virtual reality, giving credence to the view that people tend to respond realistically to virtual events and situations. From the existing literature it seems that this is likely to be the case -see for example, [Bailenson, Blascovich, Beall and Loomis 2003;Bailenson, Blascovich, Beall and Loomis 2001;Blascovich 2002;Blascovich et al 2002;Friedman et al 2007;Guye-Vuilleme et al 1999;Wilcox, Allison, Elfassy and Grelik 2006].…”
Section: If People Have This Illusion and Ifmentioning
confidence: 99%
“…A person might feel embarrassed or surprised when these rules are not adhered to and may try to back away if, for example, someone approaches them within the range of intimate distance, the inner most region in Figure 1, when this is not appropriate given the relationship between them. It has been shown that such proxemics rules tend to occur in virtual environments [Bailenson et al 2003;Bailenson et al 2001;Guye-Vuilleme et al 1999;Friedman et al 2007;Wilcox et al 2006] in relationships between people and virtual human characters, and recently it has been shown that proxemics violations generate physiological responses in people with respect to skin conductance as predicted by the theory [Llobera et al 2010]. …”
Section: ____________________________________________________________mentioning
confidence: 99%
“…Further important contributions include the work of Badler et al on animated humans [1]; Tu and Terzopolous' work on simulating fishes [27]; Blumberg and Galyean's "Silas T. Dog'" [3], Perlin and Goldberg's "IMPROV" system [23] and the work of Gratch, Johnson and Marsella [12,19]. We mostly deal with non-verbal communication, which is a major sub-field of behaviour simulation with a long research history including the work of Cassell and her group [4,5,29]; Pelachaud and Poggi [22] and Guye-Vuillème et al [11]. The two types of behaviour we are using are gesture which has been studied by Cassell et al [4] and posture which has been studied by Cassell et al [5] and by Bécheiraz and Thalmann [2].…”
Section: Related Workmentioning
confidence: 99%
“…However, though markup languages are an important step towards making it easier to specify behaviour they are a long way from the usability of graphical tools. There have also been tools for designing the content of behaviour, for example designing gestures [11], however, these tools do not address the autonomous aspects, i.e. how to decide which behaviour to perform in a given context.…”
Section: Related Workmentioning
confidence: 99%